Дослідження процесів нагріву неферомагнітного двошарового порожнистого електропровідного циліндра за дії неусталеного електромагнітного поля - Мусій, Роман; Кунинець, Андрій; Бандирський, Богдан; Орищин, Оксана; Свідрак, Інга (Kamianets-Podilskyi National Ivan Ohiienko University, 2025)
A physical and mathematical model for determining and analysing the regularities of Joule heat behaviour in a two-layer nonferromagnetic hollow conductive cylinder under nonstationary electromagnetic action is proposed. The initial relations for finding the determinant function for the axial component of the magnetic field intensity vector are given. To construct the solution, a quadratic approximation of its distributions in the constituent layers of the cylinder by the radial coordinate and the integral Laplace transform by time are applied. The expression of the axial component of the magnetic field intensity vector and the Joule heat in the component layers of the cylinder during its induction heating by an unsteady electromagnetic field is obtained. The change in the axial component of the magnetic field intensity vector and Joule heat in time and their distribution over the thickness of the cylinder's component layers made of copper and stainless steel, depending on the duration of the unsteady electromagnetic action and the magnitude of the magnetic field intensity, are analysed numerically.